Implicature and Speech Acts in Taylor Swift’s “Love Story” : A Pragmatic Analysis - Dwi Puspita Sari; Nisa Afriyuni Setiawan; Zahra Maulida Aprianti; Tatu Siti Rohbiah (Journal of English Language and Education, 2026)
Using Grice’s theory of conversational implicature and Searle’s illocutionary taxonomy, this study examines speech acts and implicatures in Taylor Swift’s lyrics for “Love Story.” A qualitative descriptive method is applied to analyse 43 utterances, identifying the song’s implied meanings and communicative functions. The results show that assertive speech acts predominate at 58.1%, followed by directives (30.2%), expressive (25.6%), commissive (11.6%), and declaratives (2.3%); these percentages reflect frequency of occurrence and do not sum to 100% because a single utterance may realize more than one speech act simultaneously. For implicatures, classification follows criteria: Generalized Conversational Implicature (65.1%) conveys meaning understandable without specific background knowledge, whereas Particularized Conversational Implicature (34.9%) depends heavily on context and intertextual references—mainly to Shakespeare’s Romeo and Juliet and Hawthorne’s The Scarlet Letter. Combined, these pragmatic strategies construct a multi‑layered romantic narrative accessible at both universal and context‑specific levels. This study demonstrates that song lyrics constitute a rich form of pragmatic discourse, in which speech acts and implicatures interact to convey narrative meaning and emotional depth beyond literal expression.